On α-Fuzzy Soft Irreducible Spaces - Majd Hamid Mahmood (Al-Mustansiriyah Journal of Science, 2023)
We define fuzzy soft irreducible sets, a-fuzzy soft irreducible sets in fuzzy soft topological spaces and study the properties including (fuzzy soft continuity; fuzzy soft homeomorphism and fuzzy soft topological properties) on a-fuzzy soft irreducible sets.